Systematic Review - Brasil, Sandra (2022)
R.F. and acknowledge the funding from the Fundação para a Ciência e Tecnologia (FCT), Portugal. S.B. was supported by CDG & Allies—PAIN funding. M.A. acknowledges PhD program at the DISTABIF, Università degli Studi della Campania “Luigi Vanvitelli”, PhD fellowship POR Campania FSE 2014/2020 “Dottorati di Ricerca Con Caratterizzazione Industriale”.